2020
DOI: 10.1002/app.49631
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐based hydroxymethylated eugenol modified bismaleimide resin and its high‐temperature composites

Abstract: Hydroxymethylated eugenol (MEG) and poly (hydroxymethylated eugenol) (PMEG) were synthesized by the condensation reaction of eugenol (EG) with formaldehyde. The different contents of MEG and PMEG were used to modify 4,4 0-bismaleimidediphenylmethane (BMI). The cured MEG-BMI resins exhibit good thermal stability evidenced by its 5% weight loss temperatures above 407 C and its residue above 39.4% at 800 C under nitrogen. For carbon/MEG-BMI composites, their glass transition temperatures were around 400 C; their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…The latter can also be obtained by stirring HMEu at high temperatures. 99 All three compounds 45-47 were cured with BMID, and the thermal and mechanical properties of the cured resins were investigated. The cured DHDEu/BMID, HMEu/BMID, and PBMEu/BMID resins exhibited good thermal stability with T g of approximately 400 C and good flexural properties.…”
Section: Single Reactions and One-pot Process For New Eugenol-like Mo...mentioning
confidence: 99%
“…The latter can also be obtained by stirring HMEu at high temperatures. 99 All three compounds 45-47 were cured with BMID, and the thermal and mechanical properties of the cured resins were investigated. The cured DHDEu/BMID, HMEu/BMID, and PBMEu/BMID resins exhibited good thermal stability with T g of approximately 400 C and good flexural properties.…”
Section: Single Reactions and One-pot Process For New Eugenol-like Mo...mentioning
confidence: 99%
“…Bismaleimide (BMI) is a thermosetting resin with active terminal group of unsaturated maleimide ring, which has good heat resistance, durable chemical resistance and radiation resistance. [1][2][3][4][5] It can be widely used in aerospace, marine engineering, mechanical and electronic industries. [6][7][8] However, BMI tends to form a threedimensional network structure with excessive crosslinking in the curing process, leading to the rise of cross-linked density, thereby significantly reducing the toughness of the material .…”
Section: Introductionmentioning
confidence: 99%
“…They can be prepared via blending, reinforcing, and cross‐linking. Several groups have reported that modified EU‐based epoxy resins are more beneficial than the pristine EU‐based epoxy resin due to their excellent adhesions, anti‐corrosion, and rigid structure 4,6,18–20 …”
Section: Introductionmentioning
confidence: 99%